Nigerian civil war and Britain’s peace initiative, 1967–1970 (2019)
The outbreak of the Nigerian Civil War few years after the attainment of independence from Britain further deepened the interest of the latter in Nigeria’s existence as a nation. Scholars of disciplines such as history, political science and international relations through their works, have examined the nature and dimensions of Nigeria’s relations with Britain as well as the British involvement in the Nigerian Civil War. Foreign policy formulation, colonial legacies, economic ties, are typical examples of the nature of Nigeria’s relations with Britain. Similarly, scholars have interrogated the roles of Britain in the Nigerian Civil War through multilateral efforts at the United Nations and Commonwealth of Nations, propaganda, protection of the British economic interests in Nigeria, British military initiative as well as the pressure of the Cold War as the basis for prompt British intervention in the war. However, comprehensive intellectual attention has not been paid to the British peace initiative outside the multilateral conflict resolution structure. It is against this backdrop that this paper interrogates the nature and dimension of British peace initiative strategy which brought an end to the Nigerian Civil War. The paper argues in its conclusion that the failure of the multilateral approach of the British was salvaged by the unilateral British bureaucratic strategy that was enhanced by their colonial legacies in Nigeria.